Mathematical Models of Conflict Controlled Processes under Functional Self-Organization of the Respiratory System - Aralova, N.I.; Aralova, A.A. (Кибернетика и вычислительная техника, 2019)
The purpose of the paper is to build a mathematical model of a functional respiration system that simulates resolving a conflict situation between executive and managing bodies of self-regulation in the conflict for oxygen, which allows predicting the parameters of selforganization of the respiratory system under internal and external disturbances. Results. A mathematical model of mass transfer and mass transfer of respiratory gases in the human body is presented in the form of a system of non-linear differential equations, which is a controlled dynamic system, the state of which is determined at each time point by oxygen and carbon dioxide stresses in each structural link of the respiratory system (alveoli, blood and tissues). Мета. Побудувати математичну модель функціональної системи дихання, яка імітує розв’язання конфліктної ситуації між керувальними та виконавчими органами саморегуляції у боротьбі за кисень, яка надає можливість прогнозувати параметри самоорганізації системи дихання за внутрішніх та зовнішніх збурень. Результати. Надано математичну модель масопереносу та масообміну респіраторних газів в організмі людини як систему диференційних рівнянь, яка є керованою динамічною системою, стани якої визначаються у кожен момент напруженнями кисню та вуглекислого газу в кожній структурній ланці системи дихання (альвеолах, крові, тканинах). Цель. Построить математическую модель функциональной системы дыхания, имитирующую разрешение конфликтной ситуации между исполнительными и управляющими органами саморегуляции в борьбе за кислород, которая позволяет прогнозировать параметры самоорганизации системы дыхания при внутренних и внешних возмущениях. Результаты. Представлена математическая модель массопереноса и массообмена респираторных газов в организме человека в виде системы нелинейных дифференциальных уравнений, являющую собой управляемую динамическую систему, состояние которой определяется в каждый момент времени напряжениями кислорода и углекислоты в каждом структурном звене системы дыхания (альвеолах, крови и тканях).